Overexpression of PLXDC2 in Stromal Cell-Associated M2 Macrophages Is Related to EMT and the Progression of Gastric Cancer - Guan, Yiming; Du, Yuzhang; Wang, Guanzheng; Gou, Hongquan; Xue, Yilun; Xu, Jingsong; Li, Enhao; Chan, David W.; Wu, Di; Xu, Peiqing; Ni, Peihua; Xu, Dakang; et al. (Frontiers in Cell and Developmental Biology, 2021)
The tumor microenvironment (TME) comprises distinct cell types, including stromal types such as fibroblast cells and macrophage cells, which have recently become a critical factor in tumor development and progression. Here, we identified the TME-related gene, plexin domain containing 2 (PLXDC2), in a high-stromal-score population. And we revealed that this gene was related to poor survival and advanced TNM (tumor-node-metastasis) stage in gastric cancer (GC) patients from The Cancer Genome Atlas (TCGA) database. An integrated gene profile and functional analysis of the proportions of tumor-infiltrating immune cells (TICs) revealed that the expression of the M2 macrophages cell marker CD163 was positively correlated with PLXDC2 expression. In addition, the M2 macrophages gene signature and high PLXDC2 expression were associated with the inflammatory signaling pathway and the epithelial-to-mesenchymal transition (EMT)-related gene signature. Single-cell study of GC identified PLXDC2 was enriched specifically in fibroblasts and monocytes/macrophages populations, which supported its important role in the stroma. Furthermore, according to a tissue microarray (TMA) immunohistochemistry analysis, the expression of PLXDC2 elevated in human GC stromal specimens compared to tumor tissue specimens. Moreover, PLXDC2 overexpression in the stromal compartment was associated with CD163-positive regulatory M2 macrophages, and its functions were related to the pathogenesis of GC. Multiplexed immunohistochemistry (mIHC) verified PLXDC2’s correlation with EMT markers. Our data suggest that PLXDC2 was expressed in stromal cells and that its crosstalk with tumor-associated macrophages could contribute to cancer biology by inducing the EMT process.